Service Recovery Strategies for Satisfaction in Thai Tourists Experiencing Service Failures Caused by Hostels - Tanadtanusilp , Pattaraporn; Vannavanit , Yupawan (Dusit Thani College Journal, 2020)
This research aimed 1) to study experience of Thai tourists about service failures in hostel services and 2) to analyze the effective of service recovery strategies for satisfaction in hostel services. Research methodology used quantitative and qualitative research. The questionnaires were used for data collection taken from the sample 385 of Thai tourists who used to use hostel services. The in-depth interviews with 5 hostel entrepreneurs and 5 tourists who used to use hostel services. The data analysis including were frequency, percentage, standard deviation, comparing the differences with Paired-sample t-test at the statistical significance level at 0.01 and content analysis. The result of the study shows that the sample used to experience the most common in service delivery at 92.73%, staff services at 83.38% and customers’requests at 83.12% respectively. Level of satisfaction after use service recovery strategies is higher than level of satisfaction before use service recovery strategies at the statistical significance level at 0.01. The comparison of satisfaction after using the strategies revealed that problem-solving skill of staff was in higher relative level of satisfaction at 50.63% followed by discount or refund at 48.32%, promptly dealing with complaints at 38.54% and saying apology at 30.02%.